Prove that - (secA+tanA)/(secA-tanA)=tan^2((pi/4)+(A/2)) 06:57 Prove that : (secA+1)/(tanA)=(tanA)/(secA-1) 01:10 Prove that : (secA-tanA)/(secA+tanA)=1-2secAtanA+2tan^(2)A 05:01 Prove that : (tanA+sinA)/(tanA-sinA)=(secA+1)/(secA-1) 01:52 सिद...
Prove that : (i) (1)/(1-cosA)+(1)/(1+cosA)=2"cosec"^(2)A " " (ii) (1)/(1-sinA)-(1)/(1+sinA)=2secAtanA
We know that: cotA=1tanA,cotB=1tanB,cotC=1tanC Thus, we can express the left side of the equation as: (tanA+tanB+tanC)(1tanA+1tanB+1tanC) Step 2: Simplify the expression This can be simplified to: (tanA+tanB+tanC)(tanBtanC+tanCtanA+tanAtanBtanAtanBtanC) ...
If cos e cA+secA=cos e c B+s e cB , prove that: "tanAtanB"=cot(A+B)/2 04:01 If ("tan"(theta+alpha))/a=""("tan"(theta+beta))/b=""("tan"(theta+gamma... 10:41 If cos A+cosB=1/2 and sin A+ sinB=1/4 , prove that: tan((A+B)/2)=1/2 02:39 If asintheta...
Step by step video & image solution for Prove : (sinA+cosecA)^(2)+(cosA+secA)^(2)=7+tan^(2)A+cot^(2)A. by Maths experts to help you in doubts & scoring excellent marks in Class 10 exams. Updated on:21/07/2023 Class 10MATHSTRIGONOMETRIC RATIOS AND IDENTITIES ...
Prove that :(secA+tanA)(1−sinA)=cosA View Solution Porve that : (cosecA-sinA)(secA-cosA)=1tanA+cotA View Solution Free Ncert Solutions English Medium NCERT Solutions NCERT Solutions for Class 12 English Medium NCERT Solutions for Class 11 English Medium ...
Prove that :(secA+tanA)(1−sinA)=cosA View Solution Prove that:sin2A1+cos2A=tanA View Solution Doubtnut is No.1 Study App and Learning App with Instant Video Solutions for NCERT Class 6, Class 7, Class 8, Class 9, Class 10, Class 11 and Class 12, IIT JEE prep, NEET preparation...
View Solution cosec A + cot A=a and cosec A - cot A=b then View Solution cosec2A+cosec2B+cosec2C=0হলে দেখাও যে,tanA+tanB+tanC+cotA+cotB+cotC=0 View Solution Exams IIT JEE NEET UP Board Bihar Board ...